2019
DOI: 10.1016/j.jacc.2019.03.496
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Aortic Valve Replacement in Patients With End-Stage Renal Disease

Abstract: Objectives: To examine whether transcatheter aortic valve replacement (TAVR) is a safe and effective treatment option for aortic stenosis in patients with end-stage renal disease (ESRD). Background: Patients with ESRD undergoing surgical aortic valve replacement have an operative mortality approaching 20% and a 10-year survival of approximately 12%. We investigated whether TAVR is a more reasonable option. Methods: This is a multicenter, retrospective study of all patients with ESRD who underwent TAVR in 8 ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 43 publications
9
65
1
1
Order By: Relevance
“…Likewise, patients undergoing dialysis had a higher 1-year mortality (37% vs. 19%; P < 0.01) and a higher rate of major bleeding (1.4% vs. 1.0%; P ¼ 0.03) in 3053 (4.2%) of >72,000 patients in the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapies registry. 73 Analogous findings were identified in another group of dialysis patients undergoing TAVR, who had a 1-year mortality rate of 39%, compared with a 17.5% rate in those with CKD G3a (eGFR between 45-59 ml/min per 1.73 m 2 ). 65 This mortality rate appears to be further amplified by the presence of atrial fibrillation, with 1-year mortality rates as high as 71%.…”
Section: Managementmentioning
confidence: 56%
“…Likewise, patients undergoing dialysis had a higher 1-year mortality (37% vs. 19%; P < 0.01) and a higher rate of major bleeding (1.4% vs. 1.0%; P ¼ 0.03) in 3053 (4.2%) of >72,000 patients in the Society of Thoracic Surgeons/American College of Cardiology Transcatheter Valve Therapies registry. 73 Analogous findings were identified in another group of dialysis patients undergoing TAVR, who had a 1-year mortality rate of 39%, compared with a 17.5% rate in those with CKD G3a (eGFR between 45-59 ml/min per 1.73 m 2 ). 65 This mortality rate appears to be further amplified by the presence of atrial fibrillation, with 1-year mortality rates as high as 71%.…”
Section: Managementmentioning
confidence: 56%
“…One of the studies showed that most patients with ESRD have numerous comorbidities along with experiencing effects of advanced AS and prognosis of ESRD patients is highly affected by the presence of other comorbidities and their functional status. Comorbidities like peripheral vascular disease, coronary artery disease, CHF, and diabetes are associated with nearly 50% one-year survival in elderly patients on dialysis [4]. Another meta-analysis suggested that the occurrence of RF requiring hemodialysis following TAVR is related to baseline comorbidities instead of the amount of contrast used [12].…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with ESRD have numerous comorbidities along with experiencing the effects of advanced AS. The prognosis of ESRD patients is affected by the presence of comorbidities like peripheral vascular disease, CAD, congestive heart failure (CHF), diabetes, and chronic pulmonary disease with nearly 50% one-year survival in elderly patients on dialysis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is no information as to whether patients underwent HD via an AVF/ arteriovenous graft, a tunneled central catheter or arterial superficialization in the studies. The mortality rates in the short-term (30 days/1 year) and long-term (2 years/3 years) periods after TAVI are 0 to 15.2%/0 to 45.2% and 53%/73.2%, respectively [5,15,23,[25][26][27][28][29]. At present, the Japanese healthcare system does not reimburse TAVI for dialysis patients.…”
Section: The Impact Of Tavi In Dialysis Patientsmentioning
confidence: 99%